(untitled) (Research, Society and Development, 2025)
This study aims to analyze the role of nursing, highlighting its importance in the care of elderly individuals with diabetes mellitus. It seeks to clarify the main actions directed toward health promotion, prevention of complications, and improvement of the quality of life of this population. The study is based on an integrative literature review with a qualitative and quantitative approach, developed from the analysis of scientific publications between 2019 and 2025, available in the databases SciELO, Scopus, Web of Science, LILACS, PubMed, and the CAPES Periodicals Portal.The impact of this study demonstrated that nursing care goes beyond medication administration; it encompasses continuous follow-up, encouragement of self-care, health education, and humanized support. It emphasized the nurse’s approach in the early identification of complications, as well as in educational strategies that contribute to therapeutic adherence and, consequently, glycemic control. Thus, it concludes that through continuing education and the planning of individualized actions, nursing practice is strengthened, resulting in comprehensive, effective care centered on the needs of elderly individuals with diabetes.